Prospective evaluation of methylated SEPT9 in plasma for detection of asymptomatic colorectal cancer. Issue 2 (13th February 2013) - Church, Timothy Robert; Wandell, Michael; Lofton-Day, Catherine; Mongin, Steven J; Burger, Matthias; Payne, Shannon R; Castaños-Vélez, Esmeralda; Blumenstein, Brent A; Rösch, Thomas; Osborn, Neal; Snover, Dale; Day, Robert W; et al.
Abstract : Background: As screening methods for colorectal cancer (CRC) are limited by uptake and adherence, further options are sought. A blood test might increase both, but none has yet been tested in a screening setting. Objective: We prospectively assessed the accuracy of circulating methylated SEPT9 DNA (mSEPT9) for detecting CRC in a screening population. Design: Asymptomatic individuals ≥50 years old scheduled for screening colonoscopy at 32 US and German clinics voluntarily gave blood plasma samples before colon preparation. Using a commercially available assay, three independent blinded laboratories assayed plasma DNA of all CRC cases and a stratified random sample of other subjects in duplicate real time PCRs. The primary outcomes measures were standardised for overall sensitivity and specificity estimates. Results: 7941 men (45%) and women (55%), mean age 60 years, enrolled. Results from 53 CRC cases and from 1457 subjects without CRC yielded a standardised sensitivity of 48.2% (95% CI 32.4% to 63.6%; crude rate 50.9%); for CRC stages I–IV, values were 35.0%, 63.0%, 46.0% and 77.4%, respectively. Specificity was 91.5% (95% CI 89.7% to 93.1%; crude rate 91.4%). Sensitivity for advanced adenomas was low (11.2%). Conclusions: Our study using the blood based mSEPT9 test showed that CRC signal in blood can be detected in asymptomatic average risk individuals undergoing screening. However, the utility of the test for population screening for CRC will require improved sensitivity for detection of early cancers and advanced adenomas. Clinical Trial Registration Number: NCT00855348